PERPADUAN ANTARA PROPELLER DAN DAUN KEMUDI GUNA MENGOPTIMALKAN PROLPULSI DAN MANUVER KAPAL SERTA EFFISIENSI BAHAN BAKAR - Ridwan, Mohd (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2009)
Operational of ship influences the running cost. A old ship, day by day cash cost are higher with ageing machinery requiring constant maintenance, a rusty hull requiring regular steel replacement and high fuel oil consumption. Fuel cost are 30-45 % all of running cost. with integrated between propeller and rudder to optimum ship propulsion and manoeuvering to reduce 4-9% vessel’s fuel oil consumption and energy efficiency